2005
DOI: 10.1242/jcs.01724
|View full text |Cite
|
Sign up to set email alerts
|

p25/Cdk5-mediated retinoblastoma phosphorylation is an early event in neuronal cell death

Abstract: In large models of neuronal cell death, there is a tight correlation between Cdk5 deregulation and cell-cycle dysfunction. However, pathways that link Cdk5 to the cell cycle during neuronal death are still unclear. We have investigated the molecular events that precede p25/Cdk5-triggered neuronal death using a neuronal cell line that allows inducible p25 expression. In this system, no sign of apoptosis was seen before 24 hours of p25 induction. Thus, at that time, cell-cycle-regulatory proteins were analysed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 52 publications
(67 reference statements)
4
70
0
Order By: Relevance
“…This delocalization can be ascribed to the fact that p25 lacks the N-terminal membrane-tethering domain of p35 (see the introduction). 5 Finally, indications for cell-cycle re-entry claimed in p25 neuroblastoma cells 46 were also evident in this novel model by increased phosphorylation of the retinoblastoma protein (Figure 1, F and G). Nevertheless, of several other and typical cell-cycle markers that we have tested, none was markedly increased in p25-expressing neurons in vivo, and this line of analysis was not further pursued.…”
Section: Generation Of Inducible P25 Mice: Early Lethality and Initiasupporting
confidence: 53%
“…This delocalization can be ascribed to the fact that p25 lacks the N-terminal membrane-tethering domain of p35 (see the introduction). 5 Finally, indications for cell-cycle re-entry claimed in p25 neuroblastoma cells 46 were also evident in this novel model by increased phosphorylation of the retinoblastoma protein (Figure 1, F and G). Nevertheless, of several other and typical cell-cycle markers that we have tested, none was markedly increased in p25-expressing neurons in vivo, and this line of analysis was not further pursued.…”
Section: Generation Of Inducible P25 Mice: Early Lethality and Initiasupporting
confidence: 53%
“…[28][29][30]34 CDK5's targets include several important proteins for cell growth and death, such as STAT3, AKT, BCL-2, p53, and RB. 29,[34][35][36][37] By testing multiple CDK5 siRNAs and shRNAs, we confirmed that CDK5 knockdown sensitizes genetically variable myeloma cell lines to bortezomib and other proteasome inhibitors. This finding and its clinical relevance were further explored by the use of CDK5 inhibitors, roscovitine and SCH727965, which were demonstrated to synergize with bortezomib to induce cytotoxicity of both MM cell lines and primary MM samples.…”
mentioning
confidence: 62%
“…Immune complexes were washed three times with RIPA buffer and separated by SDS-PAGE gels. Transfer membranes were probed with indicated primary antibodies and HRP-conjugated antibody TrueBlot (eBioscience, San Diego, CA) as the secondary antibody (21). The membranes were detected by ECL, as mentioned above.…”
Section: Methodsmentioning
confidence: 99%